Fungicidal versus Fungistatic activity of five Iranian essences against fluconazole resistant Candida species - Donya Nikaein; Aghil Sharifzadeh; Ali Reza Khosravi (Shahrekord University of Medical Sciences, 2018)
Introduction: Antifungal resistant is one of the causes of high mortality rates during invasive candidiasis. Since development of new antifungal agents is limited, researchers have focused on natural products including essential oils (EOs) with antifungal properties. In immunocompromised patients fungicidal activity is of benefit. This study was designed to evaluate chemical composition and fungicidal/fungistatic activities of five Iranian EOs and against fluconazole resistant Candida species. Methods: To determine chemical composition of EOs gas chromatography-mass spectroscopy (GC/MS) was employed. Fluconazole resistant Candida species were chosen and minimum inhibitory concentration (MIC) values of studied EOs were determined by broth microdilution method. Minimum fungicidal concentration (MFC) was determined as the lowest concentration with no fungal growth on solid media. Fungicidal activity was calculated by MFC/MIC ratio. Results: The results showed that C. albicans and C. tropialis isolates were susceptible to itraconazole (ITC) and voriconazole (VRC) while one species of C. glabrata and C. krusei each was resistant to itraconzaole; and itraconazole resistant C. glabrata isolate was resistance to voriconzaole as well. Among tested EOs, the ones from Cinnamomum cayennense, Origanum majorana var. majoranoides and Andropogon citratus had the highest anti-Candida activity. Artemisia aromatica A. Nelson had the highest MIC value against Candida isolates. All EOs in this study had fungicidal activity. Conclusion: In general, the tested natural compounds are suitable to be used as anti-Candida. However more studies are needed on each chemical compound to evaluate its antifungal activity alone or in combination with other agents.